2013
DOI: 10.1149/2.034306jes
|View full text |Cite
|
Sign up to set email alerts
|

Solid Oxide Fuel Cells with Symmetrical Pt-YSZ Electrodes Prepared by YSZ Infiltration

Abstract: Platinum electrodes for high temperature electrochemical devices (solid oxide fuel cells, solid oxide electrolyzer cells and sensors) generally show limited performances due to confinement of triple phase boundaries (TPBs) to the Platinum-electrolyte interface. Performance degradation as a result of TPB length loss due to the microstructural instability of the Platinum electrodes at operational temperatures is the other major problem. Infiltration of yttrium stabilized zirconia (YSZ) into porous Platinum elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Figure 1 shows a flow chart, demonstrating the various stages of GDC, LCFCr and GDC+LCFCr precursor preparation. To synthesize the infiltrates, a polymeric GDC precursor was prepared by dissolving gadolinium (III) nitrate hexahydrate and cerium (III) nitrate hexahydrate in the desired stoichiometric molar ratio of cations of 0.2:0.8 (Gd:Ce) in water and ethylene glycol, 13,14 followed by stirring on a hot plate at 80…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows a flow chart, demonstrating the various stages of GDC, LCFCr and GDC+LCFCr precursor preparation. To synthesize the infiltrates, a polymeric GDC precursor was prepared by dissolving gadolinium (III) nitrate hexahydrate and cerium (III) nitrate hexahydrate in the desired stoichiometric molar ratio of cations of 0.2:0.8 (Gd:Ce) in water and ethylene glycol, 13,14 followed by stirring on a hot plate at 80…”
Section: Methodsmentioning
confidence: 99%
“…For these reasons, efforts were made to infiltrate an interconnected ionically conducting phase (gadolinia-doped ceria, GDC) into the LCFCr scaffold to improve the overall ionic conductivity of the catalyst layer. This was done by utilizing a polymeric precursor infiltration technique, shown earlier [11][12][13][14] to lead to the deposition of a thin film of the infiltrate on the surface of the scaffold particles. Since most mixed conducting electrode materials exhibit a relatively high electronic conductivity, but lack oxygen ion conductivity, 15 the formation of an interconnected ionically conducting thin film on the LCFCr particle surfaces using this technique should significantly enhance oxygen ion transport.…”
mentioning
confidence: 99%
“…There have been several reports in the literature regarding Pt/SE composite thin lm electrodes, where SE oxide serves as a physical protection layer against Pt agglomeration and/or an oxygen ion current pathway so as to maximize the TPB site density. For example, Buyukaksoy et al attempted to coat the surfaces of Pt thin lm electrodes by the inltration of yttria-stabilized ZrO 2 (YSZ), showing improved thermal stability at extremely high temperatures (>800 C) for over 200 h. 25 On the other hand, Hertz et al fabricated nanocomposite Pt/YSZ thin lm electrodes by means of magnetron co-sputtering, exhibiting an area-specic resistance (ASR) of the resulting composite lms of less than 500 U cm 2 at 400 C. 26 Chang et al also reported an enhanced power density by 2.5 times through the application of ALD-coated thin YSZ layers onto porous Pt electrodes. 24 It should be noted, however, that most relevant studies focused only on Pt/YSZ composite structures, and the fabrication methods employed appear tedious and costly.…”
Section: Introductionmentioning
confidence: 99%
“…(1) ALD oxide on metallic cathode ALD oxide overlayers (or overcoatings, capping layers), e.g., MnO x [31], ZrO 2 [28], SnO 2 [29], doped ZrO 2 [30,32], CeO x [33], on metal cathodes have been actively researched in recent years [28][29][30][31][32] because they can compensate for the low thermal stability of porous metal electrodes, and in some cases, can also improve the ORR activity. While oxide overlayers can be fabricated by using other techniques (sputtering [136][137][138], infiltration [139][140][141]), the conformal nature of the ALD process may further help to enhance the stability of metallic electrodes. The stabilization mechanism of metal nanoparticles by the oxide overlayer may include: (1) anchoring of metallic nanoparticles to the substrate, (2) stabilization of unstable metal surface atoms, which may impede the physical merging, and (3) Ostwald ripening of metallic nanoparticles [136,[142][143][144][145][146].…”
Section: Cathodementioning
confidence: 99%